Anaesthetic Management of Two Patients with Pompe Disease for Caesarean Section - I. J. J. Dons-Sinke; M. Dirckx; G. P. Scoones (Case Reports in Anesthesiology)
The introduction of enzyme replacement therapy and the resultant stabilisation or improvement in mobility and respiratory muscle function afforded to patients with late-onset Pompe may lead to an increased number of Pompe patients prepared to accept the challenges of parenthood. In this case report, we describe our anaesthetic management of two patients with Pompe disease for a caesarean section.